Development of a Software for Design and Design Comparison of Prestressed I-Beam for Highway and Railway Bridges Based on International Standards - Yucel, Mustafa Can; Akdoganbulut, Dilara; Caner, Alp (Proceedings of the International Conference on Civil Infrastructure and Construction (CIC), 2020)
New computer software is being developed within Bridgewiz R&D Co. for the aim of rapidly comparing design solutions for a prestressed I-beam (highway or railway bridge) according to different international specifications. The software will perform a series of beam designs based on user inputs and then make a comparison in terms of dimensions, material quantities, and total costs (using either user-defined or autoacquired unit prices). The design and comparison results will be presented to the user in the form of a PDF report (as well as an on-screen window) which includes tables and charts for easy visualization. The initial specifications that are planned to be included in the software are AASHTO-LRFD, EUROCODE, and Turkish Highway Bridge Specifications for highway bridges and AREMA, EUROCODE, and Turkish Railway Bridge Specifications for railway bridges. Fresh engineers will be able to use the program for verifying their designs and experienced engineers can utilize the program for staying up-to-date with requirements of contemporary specifications. The parameters that will be designed by the software are the optimum number of girders, their geometry, girder lateral spacing, number of prestressing tendons and jacking forces (taking the losses into account), prestressing tendon distribution, deck reinforcement area, and deck section stresses. The development is supported by KOSGEB - a Turkish government organization for supporting micro and small companies on research and development projects.